2023
DOI: 10.3389/fphar.2022.1066279
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin-1β increases glucose uptake and promotes GLUT4 translocation in palmitate-treated C2C12 myotubes by activating PI3K/AKT signaling pathway

Abstract: Insulin resistance (IR) is a feature of type 2 diabetes (T2DM) accompanied by reduced glucose uptake and glucose transporter 4 (GLUT4) translocation by skeletal muscle. Neuregulin-1β (NRG-1β) is essential for myogenesis and the regulation of skeletal muscle metabolism. Neuregulin-1β increases insulin sensitivity, promotes glucose uptake and glucose translocation in normal skeletal muscle. Here, we explored whether Neuregulin-1β increased glucose uptake and GLUT4 translocation in palmitate (PA)-treated C2C12 my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…15 Insulin induces downstream IRS-1 phosphorylation by stimulating INSR phosphorylation on the cell surface of skeletal muscle, which subsequently activates the PI3K/AKT signaling pathway mediating GLUT4 membrane translocation. 31 Reduced GLUT4 translocation is the direct cause of insulin resistance, 19 and we found that F4-treated IR-L6 cells displayed a tremendous increase in glucose uptake and a significant increase in muscle glycogen content, as well as a rise in GLUT4 expression and membrane translocation in skeletal muscle cells. All these results suggest that F4 ameliorates insulin resistance in skeletal muscle.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…15 Insulin induces downstream IRS-1 phosphorylation by stimulating INSR phosphorylation on the cell surface of skeletal muscle, which subsequently activates the PI3K/AKT signaling pathway mediating GLUT4 membrane translocation. 31 Reduced GLUT4 translocation is the direct cause of insulin resistance, 19 and we found that F4-treated IR-L6 cells displayed a tremendous increase in glucose uptake and a significant increase in muscle glycogen content, as well as a rise in GLUT4 expression and membrane translocation in skeletal muscle cells. All these results suggest that F4 ameliorates insulin resistance in skeletal muscle.…”
Section: Discussionmentioning
confidence: 68%
“…Among the main target organs of insulin, skeletal muscle is responsible for the uptake and metabolism of up to 80% of postprandial glucose, indicating that it is necessary to regulate systemic glucose homeostasis . Insulin induces downstream IRS-1 phosphorylation by stimulating INSR phosphorylation on the cell surface of skeletal muscle, which subsequently activates the PI3K/AKT signaling pathway mediating GLUT4 membrane translocation . Reduced GLUT4 translocation is the direct cause of insulin resistance, and we found that F4-treated IR-L6 cells displayed a tremendous increase in glucose uptake and a significant increase in muscle glycogen content, as well as a rise in GLUT4 expression and membrane translocation in skeletal muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscle is the main target of Adipo and a major location of AdipoR1. Although skeletal muscle is considered to be one of the targets of pharmacological treatment for IR or diabetes ( Dong et al, 2021 ; Wei et al, 2021 ; Yu et al, 2022 ), some studies have shown that acupuncture ST36 may stimulate skeletal muscle and improve the recovery of behavioral activity in rats subjected to cerebral ischemia or reperfusion injury ( Yang et al, 2022 ). Sun demonstrated that acupuncture at ST36 increased motor cortical excitation ( Sun et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among the main target tissues of insulin resistance, skeletal muscles are responsible for ingesting and metabolizing over 80% of glucose, making it an important tissue for regulating glucose homeostasis [31]. Insulin stimulates the insulin receptor on the skeletal muscle cells, which subsequently activates the PI3K/Akt signaling pathway to mediate GLUT4 membrane translocation [32]. Reduction in GLUT4 was the direct cause of insulin resistance [33].…”
Section: Discussionmentioning
confidence: 99%